The Role of CEO experience and CEO multiple directorships in Palestinian firm performance: the moderating effect of political connection - Saleh, Mohammed W. A.; Abdul Latif, Rohaida; Abu Bakar, Fathiyyah (Akademia Baru, 2018)
There is little doubt that political environment issues have tremendously affected application of corporate governance. Palestine experienced instability in the political situation due to Israeli occupation and for the pluralism of its party structure (Fatah is the ruling party and Hamas the opposition party). Hence, political connection serves as unique kind of external resources which can enhance the firm's performance, through political mechanisms, companies attempt to create for itself an environment that is better for its interest. The CEO characteristics play major role in the Palestinian firms and have been seen among the most important factors to enhance the firm’s performance. Many companies excelled as a result of their CEOs attributes. However, previous studies document mix and inconclusive results on CEO characteristics and firm performance. This paper provides conceptual arguments that allow for better understanding of the role of political connection on the relationship between CEO experience and firm performance. For companies, this study proposes that they should put more efforts on enhancing the role and the quality of the CEOs. Besides providing suggestions for future research, this study provides several recommendations to the Palestinian Capital Market Authority and PSE to improve its rule and regulation with respect to CG mechanisms.